Adaptation and Use of a Five-Task Model for Evaluability Assessment - Watts, Brad R.; Washington, Heather M. (Journal of MultiDisciplinary Evaluation, 2016)
Background: Over four decades have passed since the concept of evaluability was introduced; however, the availability and accessibility of methodology, frameworks, checklists and other guidance on evaluability assessments remains limited (Smith, 2005). Evaluators who wish to conduct an evaluability assessment must adopt one of few existing models or operate without guidance. This case provides an example of one model and how it was utilized to conduct an evaluability assessment of an ongoing program intervention. Purpose: This article provides a real-world example of how an evaluability assessment was conducted using a five-task model from the criminal justice field. Setting: A criminal justice program operating with at-risk adolescent youth and police officers who patrol their neighborhoods. Intervention: NA Research Design: NA Data Collection and Analysis: The original evaluability assessment collected data through interviews with program personnel, observations by the evaluability researchers, and analysis of survey data provided by the program (i.e., program participants’ responses to survey questions about the program). Findings: The evaluability assessment conducted in this case study example identified multiple changes necessary for the program to be evaluable. Technical assistance was provided in order to support the efforts of the program to prepare for evaluation, though, the evaluability assessment identified risks and costs for the program to consider prior to proceeding. The findings were developed through a five-task process, which evaluators may be able to adapt for use with other types of programs undergoing evaluability assessment.